2012
DOI: 10.1038/cddis.2012.177
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling-nanotube direction determination in neurons and astrocytes

Abstract: A tunneling nanotube (TNT) is a newly discovered structure involved in cell–cell communication and is found in various types of cells. Here we identify S100A4 as an extracellular molecule and describe its role in attracting the growth direction of TNTs. Together with its putative receptor, receptor for advanced glycation end product, we demonstrate their involvement in TNT direction guidance. Our results further suggest a mechanism for direction guidance of TNTs. In TNT-initiating cells, p53 activates caspase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 48 publications
1
84
0
5
Order By: Relevance
“…This difference may be explained in three ways: (1) different levels of RFP/EGFP expression; (2) inhibited proliferation of glioma cells which then decreased the chance of TNTs encountering them; and (3) molecules secreted by the target cells determined the direction of TNT growth [4] , i.e., different kinds or levels of molecules secreted by astrocytes and glioma cells could differentially attract…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be explained in three ways: (1) different levels of RFP/EGFP expression; (2) inhibited proliferation of glioma cells which then decreased the chance of TNTs encountering them; and (3) molecules secreted by the target cells determined the direction of TNT growth [4] , i.e., different kinds or levels of molecules secreted by astrocytes and glioma cells could differentially attract…”
Section: Discussionmentioning
confidence: 99%
“…Similar structures had been described in Drosophila imaginal discs in 1999 [2] . TNTs have been found in various types of cells, such as THP1 monocytes [3] , rat astrocytes and neurons [4] , PC12 cells [1,5] , DU 145 prostate cancer cells [6] , HEK293 cells [1,7] , hematopoietic stem cells and progenitor cells [8] , mouse macrophage J774 cells [9] , TRVb-1 cells [10] , human endothelial progenitor cells [11] , T-cells [12] , natural killer cells [13] , human monocyte-derived macrophages [9,14] , and human mesothelioma cells [15,16] . Studies have shown that TNTs can transfer a wide range of substances, such as cellular organelles [5,[17][18][19] , polyglutamine aggregates [20] , H-Ras [21] , MHC class I molecules [22] , Ca 2+ [3,23,24] , and even human immunodeficiency virus and PrP Sc [12,[25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that the small calcium binding protein S100A4 has a role in guiding TNTs as well as its potential receptor (receptor for advanced glycation end products) [112]. For TNTs between astrocytes, S100A4 was sufficient.…”
Section: (D) Direction Determination In Neurons and Astrocytesmentioning
confidence: 99%
“…Between rat hippocampal neurons and astrocytes, activation of the P53/AKT/PI3K/ mammalian target of rapamycin channel by H 2 O 2 increased the development of MNTs [20]. Recently, p53/caspase 3 activation led to cleavage of small calcium-binding protein S100A4 and subsequent decreased concentration; the resulting gradient of cells with low to high concentration of S100A4 provided direction for MNT formation [21]. M-sec/ Ral/exocyst, the filopodium-dependent mechanism, could promote the formation of MNTs in cervical cancer HeLa cells [22].…”
Section: Mechanisms Involved In the Formation Of Mntsmentioning
confidence: 99%